2020
DOI: 10.1038/s41598-020-75783-2
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of HMGB1 in colorectal cancer impacts on tumor grade and survival prognosis

Abstract: The high-mobility group box-1 (HMGB1) protein is implicated in the development of various cancers and their proliferation. According to its function, HMGB1 shuttles between the cell nucleus and cytoplasm, assisting with nucleosome stabilization and gene transcription, or localizing in the cell membrane for outgrowth. The clinicopathologic and prognostic significance of these different subcellular locations and their correlation has been unclear in colorectal cancer (CRC). We found significantly higher rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…WTAP staining in colorectal tissues was practically uniform throughout all tumor cells, so we needed to only evaluate WTAP staining intensity. The intensity of nuclear staining for WTAP was assessed in CRC tissue and scored on a 4-point scale from 0 (negative) to 1 (weak), 2 (moderate), or 3 (strong) [21][22][23][24]. High WTAP expression was defined as a staining intensity of positive invasive cancer cells of 2 or 3 [22,24].…”
Section: Assessment Of Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…WTAP staining in colorectal tissues was practically uniform throughout all tumor cells, so we needed to only evaluate WTAP staining intensity. The intensity of nuclear staining for WTAP was assessed in CRC tissue and scored on a 4-point scale from 0 (negative) to 1 (weak), 2 (moderate), or 3 (strong) [21][22][23][24]. High WTAP expression was defined as a staining intensity of positive invasive cancer cells of 2 or 3 [22,24].…”
Section: Assessment Of Stainingmentioning
confidence: 99%
“…The intensity of nuclear staining for WTAP was assessed in CRC tissue and scored on a 4-point scale from 0 (negative) to 1 (weak), 2 (moderate), or 3 (strong) [21][22][23][24]. High WTAP expression was defined as a staining intensity of positive invasive cancer cells of 2 or 3 [22,24]. Each entire section was scanned and scored independently by two pathologists.…”
Section: Assessment Of Stainingmentioning
confidence: 99%
“…Moreover, a recent study showed that cytoplasmic HMGB1 expression had been associated with high-grade CRC and poor prognosis. But, there was a better survival prognosis in CRC patients with nuclear HMGB1 expression in comparison with other patients [ 13 ]. We wondered why HT29 cells infected with HSV-HMGB1 showed a different pattern of HMGB1 localization in normoxic condition.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that during hypoxia, nucleus-to-cytosol translocated HMGB1 binds to DNA, resulting in hepatocellular carcinoma proliferation [ 12 ]. However, in CRC and colorectal adenoma tissue samples, high rates of nuclear HMGB1 expression (84.0% and 92.6%, respectively) and moderate cytoplasmic HMGB1 expression (25.2% and 11.8%, respectively) have been reported [ 13 ]. Here, to determine whether oncolytic virotherapy and overexpression of HMGB1 under hypoxic conditions can affect subcellular localization of the protein and tumor cell death, we infected three colorectal cancer cell lines with a recombinant oHSV expressing HMGB1 and investigated its effects on the cell lines in in vitro normoxic and hypoxic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Upon exposure to infectious agents or endogenous danger signals, including bacteria, viruses, endotoxin (LPS), and extracellular adenosine triphosphate (ATP), immune cells can translocate HMGB1 nuclei into the cytoplasm or even extracellularly [ 8 , 30 ]. HMGB1 with different subcellular localization possesses diverse biological functions [ 31 ]. In the present study, we demonstrated that HMGB1 level in HD-11 cells after MG infection was downregulated as MG infection progressed ( Figure 1 A,B).…”
Section: Discussionmentioning
confidence: 99%